Aurora Basin, the Weak Underbelly of East Antarctica. Issue 9 (29th April 2020) - Pelle, Tyler; Morlighem, Mathieu; McCormack, Felicity S.
Abstract: The East Antarctic Ice Sheet (EAIS) has the potential to raise global sea levels by ∼52 m. Here, we model the evolution of select EAIS catchments to 2100 using three basal melt rate parameterizations and force our model with surface mass balance and ocean thermal anomalies from 10 global climate models. While the domain loses mass under low‐emission scenarios, it gains ∼10‐mm sea‐level rise equivalent ice volume (SLRe) under high‐emission scenarios. The primary region of thinning is within 50 km upstream of Totten Glacier's grounding line. Totten's glacial discharge is modulated by the migration of its grounding line, which is sensitive to brief intrusions of ocean water at temperatures higher than present. Once the grounding line is dislodged, Totten's ice velocity increases by up to 70% of present‐day values, resulting in ∼6‐mm SLRe loss from this sector. Plain Language Summary: Predicting how much the East Antarctic Ice Sheet (EAIS) will contribute to global sea‐level rise is critical to the welfare of the global community. In our study, we model a large sector of EAIS to 2100 using a variety of different ocean melting representations and include both ocean temperature and snowfall predictions taken from two suites of climate model output. We find that by 2100, increases in snowfall outweigh increases in ice loss, and this sector of the EAIS will be responsible for a 10‐mm decrease in global sea level under the highest climate warming scenarios. We find that Totten Glacier is most at risk to enhanced ocean warming, with the southernmost portion of this glacier acting as an important control on whether it loses ice or remains at its present‐day configuration. If this portion of Totten is melted, this glacier may lose enough ice mass to raise global sea levels by 6mm by 2100. Key Points: Atmospheric changes will govern East Antarctic Ice Sheet (EAIS) mass balance to 2100 EAIS is projected to lose mass under RCP2.6 but gain mass under high‐emission scenarios by 2100 Mass loss from Totten Glacier is dependent on the retention of a vulnerable 10‐km ice plain